SM-COLSARSPROT: Highly Immunogenic Supramutational Synthetic Peptides Covering the World’s Population - Patarroyo, Manuel A.; Patarroyo, Manuel E.; Pabón, Laura; Alba, Martha P.; Bermudez, Adriana; Rugeles, María Teresa; Díaz-Arevalo, Diana; Zapata-Builes, Wildeman; Zapata, María Isabel; Reyes, César; Suarez, Carlos F.; Agudelo, William; et al. (Frontiers in Immunology, 2022)
Fifty (50) ~20 amino acid-long peptides were selected from functionally-relevant SARS-CoV-2 S, M and E proteins for trial B-21 and another fifty-three (53) common ones, plus some new ones derived from the virus’ main genetic variants for complementary trial C-21. Peptide selection was based on tremendous SARS-CoV-2 genetic variability for analysing them concerning vast human immunogenetic polymorphism for developing the first supramutational, Colombian SARS-protection (SM-COLSARSPROT), peptide mixture. Specific physicochemical rules were followed, i.e. aa predilection for polyproline type II left-handed (PPIIL) formation, replacing β-branched, aromatic amino acids, short-chain backbone H-bond-forming residues, π-π interactions (n→π* and π-CH) aa interaction with π systems and molecular fragments able to interact with them, disrupting PPIIL propensity formation. All these modified structures had PPIIL formation propensity to enable target peptide interaction with human leukocyte antigen-DRβ1* (HLA-DRβ1*) molecules to mediate antigen presentation and induce an appropriate immune response. Such modified peptides were designed for human use; however, they induced high antibody titres against S, M, E parental mutant peptides and neutralising antibodies when suitably modified and chemically-synthesised for immunising sixty-one major histocompatibility complex class II (MHCII) DNA genotyped Aotus monkeys (matched with their corresponding HLA-DRβ1* molecules), predicted to cover 77.5% to 83.1% of the world’s population. Such chemically-synthesised peptide mixture represents an extremely pure, stable, reliable and cheap vaccine for Covid-19 pandemic control, providing a new approach for a logical, rational and soundly-established methodology for other vaccine development.